Managing fall armyworm (Spodoptera frugiperda J.E. Smith) using leaf residue of neem (Azadirachta indica A. Juss) on maize (Zea mays L.) under natural infestation - Ewansiha, S.U.; Enogieru, L.H.; Aigbe, U.D.; Kamara, A. (Informa UK Limited, 2023)
Fall armyworm (Spodoptera frugiperda J.E. Smith) is a pest that has established across sub-Saharan Africa, capable of causing 100% yield loss in maize. Although aqueous extracts of neem (Azadirachta indica A. Juss) are being used to manage this pest, neem leaf residue may have added beneficial effects. This investigation was conducted during April–November 2020 at the Training and Research Farm, University of Benin, Nigeria, aiming to improve maize yields by using neem leaf residue for managing fall armyworm under natural infestation. The experiment was laid out in a randomised complete block design, with four replicates. The treatments comprised five rates of freshly cut neem leaves (0, 1.0, 3.0, 5.0 and 7.0 kg m−2) applied as a mulch. All neem leaf treatments reduced the severity of plant damage caused by fall armyworm. With application of neem leaf residue, maize plants had a longer production period (95 vs. 86 d), grew taller (130–145 vs. 72 cm), had heavier seeds (250–280 vs. 170 g), higher grain yield (3800–5300 vs. 760 kg ha−1) and stover yield (3200–4600 vs. 2100 kg−1), compared with the control. Grain yield was increased by 410–600% with the use of neem leaf residue, which was likely a combined effect of the control of fall armyworm and improved soil fertility. The results of this study will be of benefit to farmers, who are recommended to grow maize with an application of 3.0 kg m−2 of freshly cut neem leaves, which was considered the minimum rate to achieve good performance.